Escaping the Capability Trap : Turning "Small" Development into "Big" Development - Campos, J. Edgardo; Randrianarivelo, Benjamina; Winning, Kay (World Bank, Washington, DC, 2014)
The international development community has been grappling with the challenges of implementing development programs and, consequently, with the design of practical approaches to attaining program objectives. This paper contributes to the emerging discussion on addressing the implementation capacity gap in developing countries. It presents the post-conflict experience of Burundi in building the capacity of its public sector to deliver basic services and demonstrates a practical approach to implementing what has been called problem-driven iterative adaptation. The Leadership for Results approach shows that a results-focused process of learning through disciplined experimentation enables local officials and stakeholders to more willingly learn and adopt new ways of doing things. This approach can be structured to address the time inconsistency between a development program and political or electoral concerns, both of which are critical to overcome implementation challenges.